2005
DOI: 10.1177/0145721705276572
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Educators

Abstract: A survey evaluating the professional characteristics and practice patterns of diabetes educators was distributed across the United States. The specific survey aims were to assess whether (1) there continues to be a growing trend among US health professionals who consider themselves diabetes educators to obtain certification as certified diabetes educators (CDEs), (2) duties/services associated with diabetes self-management training (DSMT) and medical/medication management differ between diabetes educators who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The DSN's title differs between countries – e.g. diabetes educator, diabetes specialist nurse, or diabetes nurse – as do DSNs' duties, responsibilities, and weekly case‐loads 2,5,6,10–13. Most Swedish DSNs in primary care pass a postgraduate examination as district nurse and have a formal qualification in diabetes care 14.…”
Section: Introductionmentioning
confidence: 99%
“…The DSN's title differs between countries – e.g. diabetes educator, diabetes specialist nurse, or diabetes nurse – as do DSNs' duties, responsibilities, and weekly case‐loads 2,5,6,10–13. Most Swedish DSNs in primary care pass a postgraduate examination as district nurse and have a formal qualification in diabetes care 14.…”
Section: Introductionmentioning
confidence: 99%
“…The present questionnaire survey indicated that many CDEs surveyed considered that CDEs themselves were not working sufficiently as CDEs. Previous research has shown that successful intervention by CDEs helped to improve clinical and quality of life outcomes in certain patient groups (Burke et al 2014 ; Anderson and Funnell 2008 ; Kahn et al 2012 ; Barlow et al 2005 ). However, CDEs’ activities with diabetes care have certain difficulties in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that diabetes educators needed a comprehensive understanding of diabetes pathophysiology and epidemiology (36)(37)(38)(39). Such knowledge would empower them to establish the necessary sensitivity to diabetes in the community and offer advice to prevent it (39,40).…”
Section: Diabetes Educatorsmentioning
confidence: 99%